Biomass conversion catalyst as well as preparation method and application thereof

By introducing core-shell structure and metal active phase on ZSM-5 molecular sieve, the problems of catalyst diffusion restriction and carbon deposit formation are solved, efficient biomass cracking and high-quality production of liquid products are achieved, and the service life of the catalyst is extended .

CN119318985AActive Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310867604.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-15
Publication Date
2025-01-17
Estimated Expiration
2043-07-15

AI Technical Summary

Technical Problem

ZSM-5 molecular sieve catalysts have diffusion restrictions and carbon deposit formation problems in the catalytic pyrolysis of biomass, resulting in reduced conversion and catalyst deactivation.

Method used

The biomass conversion catalyst adopts core-shell structure, through the modification of the support pore structure and the introduction of metal active phase, forms a highly active composite structure catalyst, transfers the carbon deposited production position and inhibits carbon deposited production, and improves the selectivity of monocyclic aromatic hydrocarbons and catalysts. stability.

Benefits of technology

It achieves efficient cracking and carbon deposit inhibition of biomass macromolecules, and improves the quality of liquid products and the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318985A_ABST
    Figure CN119318985A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass conversion catalyst and a preparation method and application thereof, the catalyst comprises a carrier and active metal components, and the active metal components are distributed on the surface and in pores of the carrier; the carrier is of a core-shell structure comprising an inner core and a shell layer, the inner core is a ZSM-5 molecular sieve containing micropores and mesopores, and the shell layer is a mesoporous MCM-41 molecular sieve. The invention also provides a preparation method and application of the biomass conversion catalyst. A high-activity composite structure catalyst is formed by modulation of a carrier pore channel structure and introduction of a metal active phase, multiple functions of catalytic cracking, reforming, carbon deposition inhibition and the like are integrated, efficient and accurate cracking of macromolecular compounds in raw materials is achieved in a catalytic pyrolysis reaction, meanwhile, carbon deposition is effectively inhibited, side reactions are reduced, and the service life of the catalyst is prolonged. A high-quality bio-oil product is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomass energy, and relates to a biomass conversion catalytic material and a preparation method and application thereof. Background Art

[0002] As the only renewable energy that can be directly converted into carbonaceous liquid fuel, it is of great significance to convert biomass energy into liquid fuel that can replace fossil fuel through thermochemical means. Biomass catalytic pyrolysis technology has high conversion efficiency, and the main products are liquid bio-oil, H2, small molecular hydrocarbon gas, and some solid coke and carbon deposition byproducts. The use of rapid pyrolysis can effectively improve the yield of liquid product bio-oil, and the catalytic pyrolysis reaction with the introduction of catalyst can improve the selectivity of the target product aromatic hydrocarbons. The catalytic pyrolysis reaction is mainly divided into in-situ catalytic pyrolysis (in-situ CFP) of premixing biomass feedstock and catalyst and ex-situ catalytic pyrolysis (ex-situ CFP) of separation of the two. The former has a higher feedstock conversion rate and bio-oil yield due to direct contact between the feedstock and the catalyst, and the latter can reduce the yield of catalytic byproduct carbon deposition due to the lack of direct contact between the feedstock and the catalyst, which has a protective effect on the catalyst.

[0003] One of the core technologies of biomass catalytic pyrolysis to produce bio-oil is the catalyst. At present, the commonly used catalysts in this field mainly include alkali metals and alkaline earth metals, metal oxides, zeolite molecular sieves, etc. Alkali metal and alkaline earth metal catalysts can reduce the oxygen content of liquid products, but due to their strong alkalinity, they can easily cause excessive decomposition of bio-oil, thereby reducing the yield of liquid products; metal oxide catalysts can reduce the selectivity of some oxygen-containing compounds and improve the stability of bio-oil, but the yield of liquid products is still not high; molecular sieve catalysts can promote the decomposition and conversion of macromolecular substances, thereby obtaining high-value-added aromatic hydrocarbons and improving the quality of bio-oil. This type of catalyst has excellent cracking and deoxygenation capabilities and is the focus of research on biomass catalytic pyrolysis.

[0004] ZSM-5 molecular sieve has excellent pore structure and acidic site advantages, and has received increasing attention from researchers. However, as a typical microporous molecular sieve catalyst, it has certain diffusion limitations in the catalytic pyrolysis of biomass. It is difficult for biomass macromolecular reactants to diffuse into the micropores and perform catalytic conversion reactions on the active sites, resulting in a reduced biomass raw material conversion rate and a low selectivity for the target product monocyclic aromatic hydrocarbons (reference: AJJ, AGAT, BAJF, et al. Investigation into the shape selectivity of zeolite catalysts for biomass conversion [J]. Journal of Catalysis, 2011, 279 (2): 257-268.).

[0005] Patent CN105032475A discloses a modified ZSM-5 molecular sieve catalyst and its application for biomass pyrolysis to produce light aromatics. The catalyst includes the following components by weight: 5 to 20 parts of iron oxide, 5 to 20 parts of cobalt oxide, 5 to 15 parts of molybdenum oxide, 5 to 15 parts of gallium oxide, and 30 to 80 parts of ZSM-5 molecular sieve. It also needs to be obtained through the following steps: (1) carrier pretreatment; (2) introduction of the main active component; (3) introduction of the auxiliary active component; (4) catalyst molding. By metal modification of the ZSM-5 molecular sieve catalyst and applying the modified catalyst to biomass catalytic pyrolysis, a light aromatics yield of more than 70% was obtained, and the catalyst had high stability.

[0006] Combined with the above content, it can be seen that ZSM-5 molecular sieve has been successfully used as a catalyst or catalyst carrier in the process of biomass catalytic pyrolysis reaction, but there are still certain limitations in the use process. On the one hand, ZSM-5 molecular sieve has certain diffusion restrictions on biomass macromolecules, which will lead to a decrease in the conversion rate of raw materials; on the other hand, the reaction products in the process of biomass thermal cracking are prone to the formation of carbon deposits, and carbon deposits will block the molecular sieve pores and even poison the active sites, thereby causing the catalyst to deactivate and affect the service life and performance of the catalyst. Therefore, it is necessary to further improve the ZSM-5 molecular sieve catalyst to solve the problems existing in the prior art and improve the quality of the liquid product. Summary of the invention

[0007] In view of the problems existing in the prior art, the main purpose of the present invention is to provide a biomass conversion catalyst and its preparation method and application. By adjusting the carrier pore structure and introducing the metal active phase to form a high-activity composite structure catalyst, it integrates multiple functions such as catalytic cracking, reforming and inhibition of carbon deposition, and realizes efficient and accurate cracking of macromolecular compounds in the raw materials in the catalytic pyrolysis reaction, effectively inhibits carbon deposition, reduces the occurrence of side reactions, and obtains high-quality bio-oil products.

[0008] During the research process, it was found that during the use of the existing biomass conversion catalyst, the biggest impact of the carbon deposits generated by the reaction on the biomass conversion catalyst is that it blocks the effective pores of the micropores in the catalyst, thereby reducing the catalyst reaction activity and resulting in reduced product yield and performance. Because the micropores contain more cracking active sites, they are the core position of the biomass catalytic pyrolysis reaction, but the micropores are more easily deactivated and destroyed, so protecting the micropores becomes a core issue in the preparation of catalyst modification. After research, an original concept of "transferring carbon deposit growth space" was proposed, aiming to adjust the carbon deposit generation position to the space with the least impact on the catalyst activity by regulating the catalyst, solving the problem of objectively unavoidable carbon deposit generation. The catalyst prepared by this method can transfer the generation site of carbon deposits in the catalytic reaction and inhibit the occurrence of carbon deposit generation reactions. In the catalyst preparation method of the present invention, the acid site distribution and acid amount of the catalyst are regulated by means of alkali treatment desiliconization, mesoporous shell coating, and introduction of metal active phase, which can effectively improve the selectivity of monocyclic aromatic hydrocarbons in the product, inhibit the generation of polycyclic aromatic hydrocarbons, and obtain high-quality bio-oil products.

[0009] The first aspect of the present invention provides a biomass conversion catalyst, which includes a carrier and an active metal component, wherein the active metal component is distributed on the surface and in the pores of the carrier; the carrier is a core-shell structure including an inner core and a shell layer, the inner core is a ZSM-5 molecular sieve containing two-level pores of micropores and mesopores, and the shell layer is a mesoporous MCM-41 molecular sieve; the active metal component includes a first active metal component and a second active metal component, wherein the first active metal is at least one of the elements of Group VIII, specifically one or more of Ni, Co, and Fe, preferably Ni, and the second active metal is an alkaline earth metal, specifically one or more of Mg and Ca, preferably Mg; the active metal component exists in the form of metal oxide.

[0010] Furthermore, in the above-mentioned biomass conversion catalyst, as a specific embodiment, based on the weight of the catalyst, the carrier content is 70wt% to 80wt%, the first active metal content in terms of oxide is 10wt% to 20wt%, and the second active metal component content in terms of oxide is 5wt% to 15wt%.

[0011] Furthermore, in the above-mentioned biomass conversion catalyst, as a specific embodiment, the first active metal component is concentratedly distributed inside the carrier pores; the second active metal component is mainly distributed inside the shell mesoporous MCM-41 molecular sieve pores.

[0012] Furthermore, in the above-mentioned biomass conversion catalyst, as a specific embodiment, TEM images show that the catalyst has a core-shell structure, the thickness of the mesoporous shell layer is 10 to 30 nm, and the mesoporous layer is evenly coated.

[0013] Furthermore, in the above-mentioned biomass conversion catalyst, the average pore diameter of the catalyst is 2.5-9.5 nm, preferably 3.5-6.5 nm.

[0014] Furthermore, in the above-mentioned biomass conversion catalyst, as a specific embodiment, the total amount of acid sites of the catalyst is 850-1200 μmol / g, preferably 950-1050 μmol / g, and the ratio of B acid to L acid (B / L) is 0.70-3.50, preferably 1.20-2.90.

[0015] Furthermore, in the above-mentioned biomass conversion catalyst, as a specific embodiment, the specific surface area of ​​the catalyst is 450 to 800 m 2 / g, preferably 500 to 650 m 2 / g.

[0016] Furthermore, in the above biomass conversion catalyst, the pore volume of the catalyst is 0.40 to 0.80 cm 3 / g, preferably 0.55 to 0.75 cm 3 / g.

[0017] A second aspect of the present invention provides a method for preparing a biomass conversion catalyst, comprising the following steps:

[0018] (1) Under contact conditions, ZSM-5 molecular sieve is contacted with a treating agent for treatment, the treated material is quenched, and further separated, washed, dried and calcined to obtain material A;

[0019] (2) under mixing conditions, the material A obtained in step (1), the auxiliary agent and the solvent are uniformly mixed, and then separated, washed and dried to obtain the material B;

[0020] (3) mixing the material B obtained in step (2), the long-chain quaternary ammonium salt solution, and the silicon-containing compound uniformly for reaction, and separating, washing, drying, and roasting to obtain material C after the reaction;

[0021] (4) introducing active metal components into the material C obtained in step (3) to obtain a biomass conversion catalyst.

[0022] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the treatment agent in step (1) is a quaternary ammonium base, which can be one or more of tetraethylammonium hydroxide (TEAOH), tetrapropylammonium hydroxide (TPAOH), and tetrabutylammonium hydroxide (TBPOH), preferably at least one of tetraethylammonium hydroxide and tetrapropylammonium hydroxide. Furthermore, the treatment agent is used in the form of an aqueous solution, and the concentration of the treatment agent aqueous solution is 0.1 to 2.0 mol / L.

[0023] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific implementation, the treatment temperature in step (1) is 60-80°C, the mass ratio of ZSM-5 molecular sieve to treatment agent is 1:10-1:50, and the treatment time is generally 30-60 minutes; specifically, it can be carried out under water bath heating and stirring conditions.

[0024] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific implementation, the quenching temperature in step (1) is 0-10°C, and specifically the treated material can be placed at 0-10°C for a period of time, such as 0.5-1.0h.

[0025] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the separation in step (1) is solid-liquid separation, and any of the existing means for achieving solid-liquid two-phase separation in the art can be used, such as any of filtration, centrifugal separation, etc., preferably vacuum filtration.

[0026] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the washing in step (1) is to use water to wash until the filtrate is neutral, which generally requires multiple washings, specifically 1-20 times; preferably, deionized water is used for washing.

[0027] Furthermore, in the method for preparing the biomass conversion catalyst, as a specific embodiment, the drying in step (1) is carried out at 90 to 110° C., and the drying treatment is carried out for 6 to 12 hours.

[0028] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the roasting conditions in step (1) are as follows: the roasting temperature is 550-650°C, the roasting time is 4-6h, and the roasting is carried out in an oxygen-containing atmosphere, such as in an air atmosphere.

[0029] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the auxiliary agent in step (2) is one or more of polydimethyldiallylammonium chloride (PDDA) and polyvinylpyrrolidone (PVP), preferably polydimethyldiallylammonium chloride.

[0030] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the solvent in step (2) can be an organic solvent or an inorganic solvent, preferably an organic solvent; the organic solvent can be an alcohol solution, preferably a small molecule alcohol solution, specifically an alcohol solution with a carbon number of 1-4, specifically at least one of methanol, ethanol, and propanol, preferably ethanol, and the concentration of the alcohol is 5wt% to 25wt%. The inorganic solvent can be an inorganic salt solution, such as one or more of a sodium chloride solution and a calcium chloride solution, and the mass concentration of the inorganic solvent is generally 10wt% to 30wt%.

[0031] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific implementation, the ratio of material A, auxiliary agent, and solvent in step (2) is 1g: (10-20)mL: (10-25)mL, and the concentration of the auxiliary agent is 2-3g / L.

[0032] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the separation in step (2) is solid-liquid separation, and any of the existing means for achieving solid-liquid two-phase separation in the art can be used, such as any of filtration, centrifugal separation, etc., preferably vacuum filtration.

[0033] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the washing in step (2) is to use water to wash until the filtrate is neutral, which generally requires multiple washings, specifically 1-20 times; preferably, deionized water is used for washing.

[0034] Furthermore, in the method for preparing the biomass conversion catalyst, as a specific embodiment, the drying in step (2) is carried out at 90 to 110° C. for 4 to 8 hours.

[0035] Further, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the long-chain quaternary ammonium salt in step (3) can be one or more of dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB), and octadecyltrimethylammonium bromide (STAB); preferably hexadecyltrimethylammonium bromide. The quaternary ammonium salt solution is obtained by mixing a quaternary ammonium salt, ammonia water, an organic solvent (ethanol) and water.

[0036] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the silicon-containing compound in step (3) can be selected from one or more of methyl orthosilicate, ethyl orthosilicate, sodium silicate, and silica sol, preferably ethyl orthosilicate.

[0037] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the introduction of the active metal component in step (4) can be carried out by an impregnation method, preferably a step-by-step impregnation method, in which the step-by-step impregnation method first introduces the first active metal component and then introduces the second active metal component.

[0038] Furthermore, in the method for preparing the biomass conversion catalyst, as a specific implementation, the process of introducing the active metal component in step (4) is as follows:

[0039] (4.1) under mixing conditions, a precursor solution of a first active metal is added dropwise to material C, and the addition of the precursor solution of the first active metal is stopped after material C just presents a mobile phase, and then the sample is treated under vacuum conditions until no bubbles are generated, and then stirred, and the treatment under vacuum conditions and stirring are repeated several times, generally 3-5 times, and then dried and calcined to obtain a catalyst precursor, wherein the drying is preferably performed under mixing conditions;

[0040] (4.2) Then, a precursor solution of a second active metal is added dropwise to the catalyst precursor, and then the sample is treated under vacuum conditions until no bubbles are generated in the sample, followed by stirring. The treatment under vacuum conditions and stirring are repeated several times, generally 2-4 times, and then the catalyst is obtained after drying and calcination. The drying is preferably carried out under mixing conditions.

[0041] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the precursor of the first active metal is an inorganic salt solution containing the first active metal, which can be one or more of nitrates, hydrochlorides, and sulfates, specifically one or more of nickel nitrate, cobalt nitrate, iron nitrate, iron chloride, and iron sulfate, preferably one or more of nickel nitrate, cobalt nitrate, and iron nitrate.

[0042] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the precursor of the second active metal is an organic acid salt solution containing the second active metal, and the organic acid salt is one or more of gluconate, lactate, and citrate, and specifically can be one or more of magnesium gluconate, magnesium lactate, magnesium citrate, calcium gluconate, and calcium lactate, preferably one or more of magnesium gluconate and calcium gluconate.

[0043] Furthermore, in the method for preparing the biomass conversion catalyst, as a specific embodiment, the mixing in steps (4.1) and (4.2) can adopt at least one of the existing methods for achieving uniform mixing of materials, such as stirring.

[0044] Furthermore, in the method for preparing the biomass conversion catalyst, as a specific embodiment, the stirring in step (4.1) and step (4.2) is preferably carried out under ultrasonic conditions, and more specifically the ultrasonic conditions may be 40 to 60 kHz.

[0045] Furthermore, in the method for preparing the biomass conversion catalyst, as a specific implementation, the vacuum conditions in step (4.1) and step (4.2) are generally controlled to maintain a vacuum degree of 0.05 to 0.1 MPa.

[0046] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the drying conditions in step (4.1) are: the drying temperature is generally 60-100°C, and the drying time is 8-12h; the roasting conditions are: the roasting temperature is generally 400-600°C, and the roasting time is 4-6h. The drying is preferably carried out under stirring conditions.

[0047] Furthermore, in the preparation method of the biomass conversion catalyst, as a specific embodiment, the drying conditions in step (4.2) are: the drying temperature is generally 60-100°C, and the drying time is 8-12h; the roasting conditions are: the roasting temperature is generally 400-600°C, and the roasting time is 4-6h. The drying is preferably carried out under stirring conditions.

[0048] A third aspect of the present invention provides an application of the above-mentioned biomass conversion catalyst or the biomass conversion catalyst obtained by the biomass conversion preparation method in a biomass conversion process.

[0049] A fourth aspect of the present invention provides a method for non-in-situ catalytic pyrolysis of lignin residues, wherein the lignin residue material is contacted with the above-mentioned biomass conversion catalyst or the biomass conversion catalyst obtained by the preparation method to carry out a reaction.

[0050] Compared with the prior art, the beneficial effects and technical advantages of the biomass conversion catalyst and the preparation method thereof provided by the present invention are mainly reflected in the following aspects:

[0051] 1. The biomass conversion catalyst provided by the present invention has the functions of catalytic cracking, reforming and inhibiting carbon deposition, and is particularly suitable for non-in-situ catalytic pyrolysis of lignin residue. The catalyst can transfer the site of carbon deposition in the catalytic reaction and inhibit the occurrence of carbon deposition reaction. The composite structure catalyst AT-ZSM-5@MCM-41 with micropores-disordered mesopores as the core and ordered mesopores as the shell is prepared by pre-treating ZSM-5 molecular sieves and other means, making full use of the acid sites and pore structure advantages of ZSM-5 molecular sieve catalysts, adjusting the micro-mesoporous core structure and acid site distribution by changing the type, ratio and treatment time of the treating agent, the type of auxiliary agent, the ratio and the treatment time, etc., adjusting the thickness of the ordered mesoporous shell and the total acid amount of the composite structure catalyst by changing the ratio of the external silicon source to the core; the first active metal active phase is introduced into the micro-mesoporous composite structure molecular sieve by the equal volume impregnation method, and the second active metal active phase is introduced into the mesoporous MCM-41, and the number of active sites of the catalyst and its interaction with the carrier are adjusted by changing the loading amount of the bimetallic active phase. By introducing a bimetallic active phase and combining it with a micro-mesoporous composite structure, the catalyst achieves high selectivity for aromatic hydrocarbon target products and a strong inhibitory effect on by-product carbon deposition, thereby improving the quality of the liquid product while extending the service life of the catalyst.

[0052] 2. In the catalyst preparation method provided by the present invention, by pretreating the ZSM-5 molecular sieve and introducing an additive, the long-chain quaternary ammonium salt can be better adsorbed through electrostatic interaction, which is conducive to more uniform coating of the mesoporous MCM-41, further improving the dispersion effect of the second active metal phase in MCM-41, and enhancing the interaction between the second active metal component and the MCM-41 molecular sieve.

[0053] 3. The catalyst preparation method provided by the present invention adopts a combination of "step-by-step impregnation, vacuuming, and ultrasonic treatment" to introduce active metal components, so that the metal active phase is highly dispersed and mostly distributed inside the micro-mesoporous channels rather than on the catalyst surface, which is beneficial to regulating the location where the catalytic reaction occurs.

[0054] 4. In the catalyst preparation method provided by the present invention, by introducing the second active metal component, the second active metal component interacts with MCM-41 to produce new active sites that can change the generation position of catalytic by-product carbon deposits. The BET pore structure parameter results show that the introduction of the second active metal component makes the reduction rate of the specific surface area of ​​the mesopores of the catalyst after the reaction greater than that of the micropores, indicating that more carbon deposits tend to be generated in the mesopores, which has a certain protective effect on the micropores. At the same time, the way in which the second active metal component is introduced into MCM-41 in the catalyst preparation method of the present invention is beneficial to increasing the proportion of the second active metal component in the mesopores.

[0055] 5. In the catalyst provided by the present invention, the catalytic ability of the catalyst can be improved by the high dispersion of the first active metal, the yield of the target product monocyclic aromatic hydrocarbons can be increased, and the amount of carbon deposits generated can be reduced; the introduction of the second active metal component into the basic site can improve the decarbonylation ability of the catalyst and change the location of carbon deposits. The combination of the first active metal and the second active metal component can greatly improve the catalytic performance of the catalyst, improve the product quality, and help extend the life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is the chromatogram of the liquid product after the thermal cracking reaction of the lignin residue in Comparative Example 1.

[0057] Figure 2 This is the chromatogram of the liquid product after the non-in situ catalytic pyrolysis reaction of lignin residue in Comparative Example 3.

[0058] Figure 3 This is the chromatogram of the liquid product after the non-in-situ catalytic pyrolysis reaction of lignin residue in Comparative Example 4.

[0059] Figure 4 This is a chromatogram of the liquid product after the non-in-situ catalytic pyrolysis reaction of lignin residue in Example 5.

[0060] Figure 5 Comparison of the specific surface area loss rate of the catalyst micro-mesopores in the examples / comparative examples.

[0061] Figure 6 It is a comparison of the ratio of the specific surface area loss rate of the catalyst micro-mesopores in the examples and comparative examples.

[0062] Figure 7 It is a schematic diagram of the process flow of the non-in-situ catalytic pyrolysis of biomass of the present invention. DETAILED DESCRIPTION

[0063] The specific contents and effects of the method of the present invention are further described below by means of specific examples, but the scope of the present invention is not limited thereby.

[0064] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.

[0065] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.

[0066] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0067] Unless otherwise expressly indicated, throughout the specification and claims, the term "comprise" or its variations such as "include" or "comprising" etc. will be understood to include the stated elements or components without excluding other elements or other components. In this document, all numerical values ​​of parameters (e.g., quantities or conditions) are to be understood as being modified in all cases by the term "about", regardless of whether "about" actually appears before the numerical value.

[0068] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight and pressure is gauge pressure.

[0069] In the context of this specification, any two or more embodiments of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0070] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0071] In this paper, the nitrogen isothermal adsorption and desorption test was carried out using a Micromeritics ASAP 2460 fully automatic specific surface and porosity analyzer. The Brunauer-Emmett-Teller (BET) method was used to calculate the specific surface area and pore volume of the catalyst, and the Barrett-Joyner-Halenda (BJH) method was used to obtain the pore size distribution.

[0072] In this paper, the liquid product after the non-in situ catalytic pyrolysis of lignin residue was analyzed by gas chromatography-mass spectrometry (GC / MS) of the ThermoScientific Trace DSQII model from the United States.

[0073] Catalyst evaluation test:

[0074] use Figure 7 The process described above uses lignin residue as raw material for catalyst evaluation testing, and the specific contents are as follows:

[0075] 1) tableting, crushing and sieving the prepared catalyst to obtain catalyst powder with a particle size of 40-60 mesh;

[0076] 2) Fill the feed bin with lignin residue, fill the catalytic stage reactor with a mixture of 10 g of catalyst powder and an equal volume of quartz sand, introduce carrier gas N2 to exhaust the air in the device, and at the same time heat the pyrolysis stage reactor to 550°C, the coke tank to 400°C, and the catalytic stage reactor to 600°C.

[0077] 3) After heating to the set temperature, the carrier gas flow rate is set to 600 mL / min, the feed rate of the feed bin is 5 g / h, the material enters the pyrolysis section reactor through a continuous feeding device, the pyrolysis by-product coke is collected through a coke tank, and the primary pyrolysis gas enters the catalytic section reactor equipped with the above-prepared catalyst, and reacts for 2 hours under the action of the catalyst.

[0078] 4) The liquid product was condensed by a condensation device, and the liquid product was qualitatively and quantitatively analyzed by GC / MS. The catalyst in the catalytic reactor after the reaction was collected, and the solid product was qualitatively and quantitatively analyzed by TG. The catalyst after the reaction was calcined at 500-800°C in an oxygen atmosphere for 1-3h to remove carbon deposits, and the catalyst before and after the reaction was analyzed by BET specific surface area to characterize the effect of carbon deposits as a byproduct of the catalytic reaction on the micropores and mesopores of the catalyst. The specific results are shown in Table 1.

[0079] Example 1

[0080] Catalyst preparation:

[0081] (1) Prepare 30 mL of 0.5 mol / L TEAOH alkaline solution, add 1 g of ZSM-5 molecular sieve sample, heat and stir in a 70°C water bath, quench in an ice water bath after 40 min, filter, wash with deionized water, dry at 90°C for 12 h, and calcine at 600°C for 5 h to obtain AT1-Z.

[0082] (2) A PDDA solution was prepared according to a volume ratio of 12:13, wherein the PDDA concentration was 2 g / L and the ethanol concentration in the alcohol solution was 20 wt %. 1 g of AT1-Z sample was added to 30 mL of PDDA solution and stirred to form a suspension. After stirring for 1.5 h, the suspension was filtered, washed with deionized water, and dried at 100 °C for 6 h to obtain R1-AT1-Z.

[0083] (3) Prepare a CTAB solution according to the ratio of CTAB: ammonia water: ethanol: deionized water (1 g: 4 mL: 200 mL: 250 mL), wherein the concentration of ammonia water is 25 wt%. Add 1 g of R1-AT1-Z sample to 300 mL of CTAB solution, and perform ultrasonic oscillation, heating at 35 °C, and stirring at 600 Rpm for 1 hour. Then, add 1 g of methyl orthosilicate dropwise to the solution, and stir at 35 °C for 6 hours. Filter, wash with deionized water, dry at 90 °C for 12 hours, and calcine at 600 °C for 5 hours to obtain R1-AT1-Z@M1.

[0084] (4.1) Prepare a nickel nitrate solution with a Ni content of 10 wt%, weigh 1 g of R1-AT1-Z@M1, drop 0.05 mL of nickel nitrate solution into R1-AT1-Z@M1, and stir thoroughly until there is no obvious unevenness. Repeat the steps of "dropping solution + stirring" until the sample just presents a mobile phase. At this time, a total of 1.45 mL of nickel nitrate solution is added. Evacuate the sample (vacuum degree is 0.7 MPa) until no bubbles are generated in the sample, then perform ultrasonic oscillation on the sample, repeat "vacuum + ultrasonic oscillation" 3 times, dry the sample at 90°C for 10 hours, and calcine at 600°C for 5 hours to obtain 10Ni / R1-AT1-Z@M1.

[0085] (4.2) Prepare a magnesium gluconate solution with a Mg content of 5 wt%, weigh 1 g 10Ni / R1-AT1-Z@M1, add 0.05 mL of magnesium gluconate solution to 10Ni / R1-AT1-Z@M1, stir thoroughly until there is no obvious unevenness, repeat the steps of "adding solution + stirring" until the sample just presents a mobile phase, at which time a total of 1.25 mL of magnesium gluconate solution is added. Evacuate the sample (vacuum degree is 0.6 MPa) until no bubbles are generated in the sample, then perform ultrasonic oscillation on the sample, repeat "vacuuming + ultrasonic oscillation" twice, dry the sample at 80°C for 12 h, and roast it at 550°C for 4 h to obtain 10Ni / R1-AT1-Z@5Mg / M1.

[0086] The catalyst obtained was subjected to a catalyst evaluation test, and the results were as follows: the yield of the liquid product was 39.83 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 9.56 wt%; and the yield of the by-product carbon deposition was 6.35 wt%.

[0087] Example 2

[0088] (1) Prepare 20 mL of 0.8 mol / L TPAOH alkaline solution, add 1 g of ZSM-5 molecular sieve sample, heat and stir in a water bath at 80°C, quench in an ice water bath after 30 min, filter, wash with deionized water, dry at 105°C for 10 h, and calcine at 600°C for 5 h to obtain AT2-Z.

[0089] (2) A PDDA solution was prepared in a volume ratio of 6:5 between PVP and alcohol solution, wherein the PVP concentration was 2.5 g / L and the methanol concentration in the alcohol solution was 15 wt %. 1 g of AT2-Z sample was added to 30 mL of PVP solution and stirred to form a suspension. After stirring for 1.5 h, the suspension was filtered, washed with deionized water, and dried at 105 °C for 5 h to obtain R2-AT2-Z.

[0090] (3) Prepare a STAB solution according to the ratio of STAB: ammonia water: ethanol: deionized water (1 g: 4 mL: 200 mL: 250 mL), wherein the concentration of ammonia water is 25 wt%. Add 1 g of R2-AT2-Z sample to 300 mL of STAB solution, and perform ultrasonic oscillation, heating at 35 °C, and stirring at 600 RPm for 1 hour. Then, add 1 g of tetraethyl orthosilicate dropwise to the solution, and stir at 35 °C for 6 hours. Filter, wash with deionized water, dry at 90 °C for 12 hours, and calcine at 600 °C for 5 hours to obtain R2-AT2-Z@M2.

[0091] (4.1) Prepare a cobalt nitrate solution with a Co content of 10 wt%, weigh 1 g of R2-AT2-Z@M1, drop 0.05 mL of cobalt nitrate solution into R2-AT2-Z@M1, and stir thoroughly until there is no obvious unevenness. Repeat the steps of "dropping solution + stirring" until the sample just presents a mobile phase. At this time, a total of 1.6 mL of cobalt nitrate solution is added. Evacuate the sample (vacuum degree is 0.8 MPa) until no bubbles are generated in the sample, then perform ultrasonic vibration on the sample, repeat "vacuum + ultrasonic vibration" 3 times, dry the sample at 90 ° C for 10 hours, and calcine at 600 ° C for 5 hours to obtain 10Co / R2-AT2-Z@M2.

[0092] (4.2) Prepare a calcium lactate solution with a Ca content of 7.5 wt%. Weigh 1 g of 10Co / R2-AT2-Z@M2, drop 0.05 mL of calcium lactate solution into 10Co / R2-AT2-Z@M2, stir thoroughly until there is no obvious unevenness, repeat the steps of "dropping solution + stirring" until the sample just presents a mobile phase, at which point a total of 1.45 mL of calcium lactate solution is added. Evacuate the sample (vacuum degree of 0.6 MPa) until no bubbles are generated in the sample, then perform ultrasonic oscillation on the sample, repeat "vacuuming + ultrasonic oscillation" twice, dry the sample at 90°C for 10 h, and calcine at 550°C for 4 h to obtain 10Co / R2-AT2-Z@7.5Ca / M2.

[0093] The catalyst obtained was subjected to a catalyst evaluation test, and the results were as follows: the yield of the liquid product was 40.72 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 10.37 wt%; and the yield of the by-product carbon deposition was 5.39 wt%.

[0094] Example 3

[0095] (1) Prepare 30 mL of 0.5 mol / L TBPOH alkaline solution, add 1 g of ZSM-5 molecular sieve sample, heat and stir in a water bath at 80 °C, quench in an ice water bath after 30 min, filter, wash with deionized water, dry at 105 °C for 8 h, and calcine at 600 °C for 5 h to obtain AT3-Z.

[0096] (2) A PDDA solution was prepared in a volume ratio of 8:7, wherein the PDDA concentration was 3 g / L and the ethanol concentration in the alcohol solution was 10 wt %. 1 g of AT3-Z sample was added to 30 mL of the PDDA solution and stirred to form a suspension. After stirring for 1.5 h, the suspension was filtered, washed with deionized water, and dried at 100 °C for 8 h to obtain R3-AT3-Z.

[0097] (3) Prepare a CTAB solution according to the ratio of CTAB: ammonia water: ethanol: deionized water of 1g: 4mL: 200mL: 250mL, wherein the concentration of ammonia water is 25wt%. Add 1g of R3-AT3-Z sample to 300mL of CTAB solution, and perform ultrasonic oscillation, heating at 35℃, and stirring at 600RPm for 1h. Then, add 2g of tetraethyl orthosilicate dropwise to the solution, and stir at 35℃ for 6h. Filter, wash with deionized water, dry at 90℃ for 12h, and calcine at 600℃ for 5h to obtain R3-AT3-Z@M3.

[0098] (4.1) Prepare a ferric chloride solution with an Fe content of 8 wt%, weigh 1 g of R3-AT3-Z@M3, drop 0.05 mL of ferric chloride solution into R3-AT3-Z@M3, and stir thoroughly until there is no obvious unevenness. Repeat the steps of "dropping solution + stirring" until the catalyst sample just presents a mobile phase. At this time, a total of 1.55 mL of ferric chloride solution is added. Evacuate the sample (vacuum degree is 0.7 MPa) until no bubbles are generated in the sample, then perform ultrasonic vibration on the sample, repeat "vacuum + ultrasonic vibration" 3 times, dry the sample at 90 ° C for 12 hours, and calcine at 600 ° C for 5 hours to obtain 8Fe / R3-AT3-Z@M3.

[0099] (4.2) Prepare a magnesium lactate solution with a Mg content of 7.5 wt%. Weigh 1 g of 8Fe / R3-AT3-Z@M3, drop 0.05 mL of magnesium lactate solution into 8Fe / R3-AT3-Z@M3, stir thoroughly until there is no obvious unevenness, repeat the steps of "dropping solution + stirring" until the catalyst sample just presents a mobile phase, at which point a total of 1.5 mL of magnesium lactate solution is added. Evacuate the sample (vacuum degree of 0.5 MPa) until no bubbles are generated in the sample, then perform ultrasonic oscillation on the sample, repeat "vacuuming + ultrasonic oscillation" twice, dry the sample at 90°C for 12 h, and calcine at 600°C for 4 h to obtain 8Fe / R3-AT3-Z@7.5Mg / M3.

[0100] The catalyst obtained was subjected to a catalyst evaluation test, and the results were as follows: the yield of the liquid product was 41.63 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 10.16 wt%; and the yield of the by-product carbon deposition was 5.23 wt%.

[0101] Example 4

[0102] (1) Prepare 40 mL of 1 mol / L TBPOH alkaline solution, add 1 g of ZSM-5 molecular sieve sample, heat and stir in a 60°C water bath, quench in an ice water bath after 30 min, filter, wash with deionized water, dry at 100°C for 12 h, and calcine at 600°C for 5 h to obtain AT4-Z.

[0103] (2) A PDDA solution was prepared according to a volume ratio of 10:9 of PDDA:alcohol solution, wherein the PDDA concentration was 2.5 g / L and the propanol concentration in the alcohol solution was 7.5 wt %. 1 g of AT4-Z sample was added to 30 mL of PDDA solution and stirred to form a suspension. After stirring for 1.5 h, the suspension was filtered, washed with deionized water, and dried at 100° C. for 12 h to obtain R4-AT4-Z.

[0104] (3) Prepare a TTAB solution according to the ratio of TTAB: ammonia water: ethanol: deionized water (1 g: 4 mL: 200 mL: 250 mL), wherein the concentration of ammonia water is 25 wt%. Add 1 g of R4-AT4-Z sample to 300 mL of TTAB solution, and perform ultrasonic oscillation, heating at 35°C, and stirring at 600 RPm for 1 hour. Then, add 1 g of methyl orthosilicate dropwise to the solution, and stir at 35°C for 6 hours. Filter, wash with deionized water, dry at 90°C for 12 hours, and calcine at 600°C for 5 hours to obtain R4-AT4-Z@M4.

[0105] (4.1) Prepare a nickel nitrate solution with a Ni content of 20 wt%, weigh 1 g of R4-AT4-Z@M4, drop 0.05 mL of nickel nitrate solution into R4-AT4-Z@M4, and stir thoroughly until there is no obvious unevenness. Repeat the steps of "dropping solution + stirring" until the catalyst sample just presents a mobile phase, at which time a total of 1.7 mL of nickel nitrate solution is added. Evacuate the sample (vacuum degree is 0.9 MPa) until no bubbles are generated in the sample, then perform ultrasonic oscillation on the sample, repeat "vacuum + ultrasonic oscillation" 3 times, dry the sample at 90°C for 12 hours, and calcine at 600°C for 5 hours to obtain 20Ni / R4-AT4-Z@M4.

[0106] (4.2) Prepare a calcium gluconate solution with a Ca content of 5 wt% in a beaker, weigh 1 g of 20Ni / R4-AT4-Z@M4, add 0.05 mL of calcium gluconate solution to 20Ni / R4-AT4-Z@M4, stir thoroughly until there is no obvious unevenness, repeat the steps of "adding solution + stirring" until the catalyst sample just presents a mobile phase, at which time a total of 1.2 mL of calcium gluconate solution is added. Evacuate the sample (vacuum degree of 0.6 MPa) until no bubbles are generated in the sample, then perform ultrasonic vibration on the sample, repeat "vacuuming + ultrasonic vibration" twice, dry the sample at 80°C for 12 hours, and calcine at 600°C for 4 hours to obtain 20Ni / R4-AT4-Z@5Ca / M4.

[0107] The catalyst obtained was subjected to a catalyst evaluation test, and the results were as follows: the yield of the liquid product was 45.39 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 12.94 wt%; and the yield of the by-product carbon deposition was 3.48 wt%.

[0108] Example 5

[0109] (1) Prepare 30 mL of 0.5 mol / L TPAOH alkaline solution, add 1 g of ZSM-5 molecular sieve sample, heat and stir in a water bath at 80°C, quench in an ice water bath after 40 min, filter, wash with deionized water, dry at 100°C for 10 h, and calcine at 600°C for 5 h to obtain AT5-Z.

[0110] (2) A PDDA solution was prepared according to a volume ratio of 5:9 of PDDA:alcohol solution, wherein the PDDA concentration was 2 g / L and the ethanol concentration in the alcohol solution was 6 wt %. 1 g of AT5-Z sample was added to 30 mL of PDDA solution and stirred to form a suspension. After stirring for 1.5 h, the suspension was filtered, washed with deionized water, and dried at 100 °C for 12 h to obtain R5-AT5-Z.

[0111] (3) Prepare a CTAB solution according to the ratio of CTAB: ammonia water: ethanol: deionized water of 1g: 4mL: 200mL: 250mL, wherein the concentration of ammonia water is 25wt%. Add 1g of R5-AT5-Z sample to 300mL of CTAB solution, and simultaneously perform ultrasonic oscillation, heating at 35°C, and stirring at 600RPm for 1h. Then, add 1g of tetraethyl orthosilicate dropwise to the solution, and stir at 35°C for 6h. Filter, wash with deionized water, dry at 90°C for 12h, and calcine at 600°C for 5h to obtain R5-AT5-Z@M5.

[0112] (4.1) Prepare a nickel nitrate solution with a Ni content of 20 wt%, weigh 1 g of R5-AT5-Z@M5, drop 0.05 mL of nickel nitrate solution into R5-AT5-Z@M5, and stir thoroughly until there is no obvious unevenness. Repeat the steps of "dropping solution + stirring" until the catalyst sample just presents a mobile phase. At this time, a total of 1.65 mL of nickel nitrate solution is added. Evacuate the sample (vacuum degree is 0.8 MPa) until no bubbles are generated in the sample, then perform ultrasonic vibration on the sample, repeat "vacuum + ultrasonic vibration" 3 times, dry the sample at 90 ° C for 10 hours, and calcine at 600 ° C for 5 hours to obtain 20Ni / R5-AT5-Z@M5.

[0113] (4.2) Prepare a magnesium gluconate solution with a Mg content of 7.5wt%, weigh 1g 20Ni / R5-AT5-Z@M5, add 0.05mL of magnesium gluconate solution to 20Ni / R5-AT5-Z@M5, stir thoroughly until there is no obvious unevenness, repeat the steps of "adding solution + stirring" until the catalyst sample just presents a mobile phase, at which time a total of 1.45mL of magnesium gluconate solution is added. Evacuate the sample (vacuum degree is 0.5MPa) until no bubbles are generated in the sample, then perform ultrasonic vibration on the sample, repeat "vacuum + ultrasonic vibration" twice, dry the sample at 90℃ for 10h, and roast it at 500℃ for 4h to obtain 20Ni / R5-AT5-Z@7.5Mg / M5.

[0114] The catalyst obtained was subjected to a catalyst evaluation test, and the results were as follows: the yield of the liquid product was 45.78 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 13.21 wt%; and the yield of the by-product carbon deposition was 3.01 wt%.

[0115] Figure 4The chromatogram analysis of the liquid product after the non-in-situ catalytic pyrolysis reaction of the lignin residue in Example 5: Under the catalytic action of the 20Ni / R5-AT5-Z@7.5Mg / M5 catalyst, the GC / MS products after the non-in-situ catalytic pyrolysis of the lignin residue include the target products of monocyclic aromatic hydrocarbons (benzene, toluene, xylene), polycyclic aromatic hydrocarbons (naphthalene, methylnaphthalene), phenol and dimethylphenol. Compared with the 20Ni / R5-AT5-Z@M5 catalyst, the 20Ni / R5-AT5-Z@7.5Mg / M5 catalyst has an appropriate degree of aromatization, the selectivity of monocyclic aromatic hydrocarbons in the product is further increased, and polycyclic aromatic hydrocarbons are also suppressed to a certain extent, which matches the aforementioned reduction in carbon deposit yield. The introduction of the Mg active phase brings alkaline sites, which can inhibit the further generation of carbon deposit precursors from ketene substances; the oxygen-containing products are mainly composed of phenolic substances containing only one O, including phenol and dimethylphenol, and the content of multi-side chain phenolic substances is greatly reduced. The deoxygenation ability and alkylation effect are better than those of 20Ni / R5-AT5-Z@M5 and R5-AT5-Z@M5 catalysts.

[0116] Example 6

[0117] (1) Prepare 40 mL of 0.3 mol / L TEAOH alkaline solution, add 1 g of ZSM-5 molecular sieve sample, heat and stir in a 60°C water bath, quench in an ice water bath after 40 min, filter, wash with deionized water, dry at 100°C for 12 h, and calcine at 600°C for 5 h to obtain AT6-Z.

[0118] (2) PVP solution was prepared in a volume ratio of 3:5, wherein the PVP concentration was 2 g / L and the ethanol concentration in the alcohol solution was 25 wt %. 1 g of AT6-Z sample was added to 30 mL of PVP solution and stirred to form a suspension. After stirring for 1.5 h, the suspension was filtered, washed with deionized water, and dried at 100 ° C for 12 h to obtain R6-AT6-Z.

[0119] (3) Prepare a CTAB solution in a conical flask according to the ratio of CTAB: ammonia water: ethanol: deionized water (1 g: 4 mL: 200 mL: 250 mL), wherein the concentration of ammonia water is 25 wt%. Add 1 g of R6-AT6-Z sample to 300 mL of CTAB solution, and simultaneously perform ultrasonic oscillation, heating at 35°C, and stirring at 600 RPm for 1 h. Then, add 2 g of methyl orthosilicate dropwise to the solution in the conical flask, and stir at 35°C for 6 h. Filter, wash with deionized water, dry at 90°C for 12 h, and calcine at 600°C for 5 h to obtain R6-AT6-Z@M6.

[0120] (4.1) Prepare a ferric sulfate solution with an Fe content of 15 wt%, weigh 1 g of R6-AT6-Z@M6, drop 0.05 mL of ferric sulfate solution into R6-AT6-Z@M6, and stir thoroughly until there is no obvious unevenness. Repeat the steps of "dropping solution + stirring" until the catalyst sample just presents a mobile phase. At this time, a total of 1.7 mL of ferric sulfate solution is added. Evacuate the sample (vacuum degree is 0.7 MPs) until no bubbles are generated in the sample, then perform ultrasonic vibration on the sample, repeat "vacuum + ultrasonic vibration" 3 times, dry the sample at 70 ° C for 12 hours, and calcine at 600 ° C for 5 hours to obtain 15Fe / R6-AT6-Z@M6.

[0121] (4.2) Prepare a magnesium citrate solution with a Mg content of 12.5 wt%, weigh 1 g of 15Fe / R6-AT6-Z@M6, add 0.05 mL of magnesium citrate solution to 15Fe / R6-AT6-Z@M6, stir thoroughly until there is no obvious unevenness, repeat the steps of "adding solution + stirring" until the catalyst sample just presents a mobile phase, at which point a total of 1.6 mL of magnesium citrate solution is added. Evacuate the sample (vacuum degree of 0.6 MPa) until no bubbles are generated in the sample, then perform ultrasonic oscillation on the sample, repeat "vacuuming + ultrasonic oscillation" twice, dry the sample at 90°C for 12 hours, and calcine at 600°C for 5 hours to obtain 15Fe / R6-AT6-Z@12.5Mg / M6.

[0122] The catalyst obtained was subjected to a catalyst evaluation test, and the results were as follows: the yield of the liquid product was 42.15 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 11.32 wt%; and the yield of the by-product carbon deposition was 3.89 wt%.

[0123] Comparative Example 1

[0124] In Comparative Example 1, no catalyst was loaded, only quartz sand was loaded. The lignin residue material was loaded in the feed bin, 10g of quartz sand was loaded in the catalytic stage reactor, and the carrier gas N2 was introduced to discharge the air in the reaction device. At the same time, the pyrolysis stage reactor was heated to 550°C, the coke tank was heated to 400°C, and the catalytic stage reactor was heated to 600°C. After heating to the set temperature, the carrier gas flow rate was set to 600mL / min, the feed bin feed rate was 5g / h, the material entered the pyrolysis stage reactor through a continuous feeding device, the pyrolysis byproduct coke was collected through the coke tank, and the primary pyrolysis gas entered the catalytic stage reactor filled with quartz sand. The reaction time was 2h. The liquid product was condensed by a three-stage condensation device, and the liquid product was qualitatively and quantitatively analyzed by GC / MS. The catalyst in the catalytic stage reactor after the reaction was collected, and the solid product was qualitatively and quantitatively analyzed by TG. The results after evaluation and testing are as follows: the yield of liquid product is 55.65 wt%, of which the yield of target product monocyclic aromatic hydrocarbon is 0.37 wt%.

[0125] Figure 1 Analysis of the chromatogram of the liquid product after the thermal cracking reaction of the lignin residue (Comparative Example 1): Under the condition of no catalyst, the GC / MS thermal cracking products of the lignin residue at 550°C are mainly phenolic substances containing alkyl, alkoxy and alkenyl side chains. In the thermal cracking without catalyst, the β-O-4 bond of the lignin macromolecule is mainly broken to generate phenols with multiple side chains.

[0126] Comparative Example 2

[0127] AT5-Z prepared by step (1) in Example 5 was used as a catalyst. The results of the evaluation test were as follows: the yield of the liquid product was 38.91 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 7.35 wt%; the yield of the by-product carbon deposition was 6.37 wt%.

[0128] Comparative Example 3

[0129] R5-AT5-Z@M5 was prepared by using steps (1) to (3) in Example 5 and used as a catalyst. The results after evaluation and testing were as follows: the yield of the liquid product was 38.78 wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 8.12 wt%; the yield of the by-product carbon deposition was 6.29 wt%.

[0130] Figure 2Analysis of the chromatogram of the liquid product after the non-in-situ catalytic pyrolysis reaction of lignin residue (Comparative Example 3): Under the catalytic action of R5-AT5-Z@M5, the GC / MS products after the non-in-situ catalytic pyrolysis of lignin residue include the target products of monocyclic aromatic hydrocarbons (benzene, toluene, xylene), polycyclic aromatic hydrocarbons (naphthalene, methylnaphthalene), phenol, and phenolic substances containing alkyl side chains. The R5-AT5-Z@M5 catalyst has aromatization and deoxygenation capabilities, and a large number of monocyclic aromatic hydrocarbons are generated, but the content of polycyclic aromatic hydrocarbons also increases accordingly; the oxygenated substances are mainly composed of phenolic substances containing only one O, among which the phenolic substances with polyalkane side chains (tetramethylphenol) have a higher selectivity, indicating that the alkylation effect is not good.

[0131] Comparative Example 4

[0132] 20Ni / R5-AT5-Z@M5 was prepared by using steps (1) to (4.1) in Example 5 and used as a catalyst. The results after evaluation and testing were as follows: the yield of liquid product was 39.72wt%, of which the yield of target product monocyclic aromatic hydrocarbons was 10.22wt%; the yield of by-product carbon deposition was 4.19wt%.

[0133] Figure 3 Analysis of the chromatogram of the liquid product after the non-in-situ catalytic pyrolysis reaction of lignin residue (Comparative Example 4): Under the catalytic action of the 20Ni / R5-AT5-Z@M5 catalyst, the GC / MS products after the non-in-situ catalytic pyrolysis of lignin residue include the target products of monocyclic aromatic hydrocarbons (benzene, toluene, xylene), polycyclic aromatic hydrocarbons (naphthalene, methylnaphthalene), phenol, and phenolic substances containing alkyl side chains. Compared with the R5-AT5-Z@M5 catalyst, the deoxygenation ability of the 20Ni / R5-AT5-Z@M5 catalyst is greatly improved, the selectivity of oxygenated phenolic substances in the liquid product is greatly reduced, the content of phenolic substances with polyalkane side chains is reduced, and the alkylation effect is improved. However, there are still a large number of polycyclic aromatic hydrocarbons in the product, which are easy to generate carbon deposit precursors or even carbon deposits, which is not conducive to the improvement of the quality of the catalytic product.

[0134] Comparative Example 5

[0135] R5-AT5-Z@7.5Mg / M5 was prepared by using steps (1) to (3) and (4.2) in Example 5 and used as a catalyst. The results after evaluation and testing were as follows: the yield of the liquid product was 38.10wt%, of which the yield of the target product monocyclic aromatic hydrocarbons was 8.81wt%; the yield of by-product carbon deposition was 4.99wt%.

[0136] Comparative Example 6

[0137] 20Ni / AT5-Z@7.5Mg / M5 was prepared by using steps (1), (3) to (4.2) in Example 5 and used as a catalyst. The results after evaluation and testing were as follows: the yield of liquid product was 39.26wt%, of which the yield of target product monocyclic aromatic hydrocarbons was 12.26wt%; the yield of by-product carbon deposition was 3.76wt%.

[0138] Table 1 Comparison of catalyst pore structure parameters before and after non-in-situ catalytic pyrolysis reaction

[0139]

[0140] Figure 6 The ratio of the loss rate of the specific surface area of ​​the micro-mesopores of the catalysts in different embodiments / comparative examples is compared; according to the change in the specific surface area of ​​the micro-mesopores before and after the catalyst reaction, the change in the location of the carbon deposits can be determined. For the 20Ni / R5-AT5-Z@7.5Mg / M5 catalyst of Example 5, the micropore specific surface area decreased by 14.96% and the mesopore specific surface area decreased by 20.16% after the reaction. The ratio of the loss rate of the specific surface area of ​​the micro-mesopores was 0.74, which is the lowest among several embodiments / comparative examples. This shows that under the catalytic action of the 20Ni / R5-AT5-Z@7.5Mg / M5 catalyst, the effect of carbon deposits on the specific surface area of ​​the mesopores is greater than that on the micropores, and more byproduct carbon deposits are generated in the mesopore channels, which has a protective mechanism for the active sites in the micropores, which is beneficial to improving the catalytic performance and extending the service life of the catalyst. This matches the result that the selectivity of the target product monocyclic aromatic hydrocarbons in the liquid product is greatly improved, while the selectivity of polycyclic aromatic hydrocarbons is low.

[0141] Among them, S BET and V Total represents the Brunauer-Emmett-Teller (BET) specific surface area and total pore volume calculated by the BET method; S micro and V micro is the micropore specific surface area and pore volume calculated by t-Plot method; S meso and V meso Represents mesopore specific surface area and pore volume.

Claims

1. A biomass conversion catalyst, comprising a carrier and an active metal component, wherein the active metal component is distributed on the surface and in the pores of the carrier; the carrier is a core-shell structure comprising an inner core and a shell layer, wherein the inner core is a ZSM-5 molecular sieve having two-level pores of micropores and mesopores, and the shell layer is a mesoporous MCM-41 molecular sieve; the active metal component comprises a first active metal component and a second active metal component, wherein the first active metal is at least one of the elements of Group VIII, the second active metal is an alkaline earth metal, and the active metal component exists in the form of a metal oxide.

2. The biomass conversion catalyst according to claim 1, characterized in that: The first active metal is one or more of Ni, Co, and Fe, preferably Ni, and the second active metal is one or more of Mg and Ca, preferably Mg.

3. The biomass conversion catalyst according to claim 1, characterized in that: Based on the weight of the catalyst, the carrier content is 70wt% to 80wt%, the first active metal content in terms of oxide is 10wt% to 20wt%, and the second active metal component content in terms of oxide is 5wt% to 15wt%.

4. The biomass conversion catalyst according to claim 1, characterized in that: The first active metal component is concentratedly distributed inside the carrier pores; the second active metal component is mainly distributed inside the shell mesoporous MCM-41 molecular sieve pores.

5. The biomass conversion catalyst according to claim 1, characterized in that: The catalyst has a core-shell structure, the thickness of the mesoporous shell layer is 10-30nm, and the mesoporous layer is coated evenly.

6. The biomass conversion catalyst according to claim 1, characterized in that: The average pore diameter of the catalyst is 2.5 to 9.5 nm, preferably 3.5 to 6.5 nm.

7. The biomass conversion catalyst according to claim 1, characterized in that: The total amount of acid sites of the catalyst is 850 to 1200 μmol / g, preferably 950 to 1050 μmol / g, and the ratio of B acid to L acid is 0.70 to 3.50, preferably 1.20 to 2.

90.

8. The biomass conversion catalyst according to claim 1, characterized in that: The specific surface area of ​​the catalyst is 450-800m 2 / g, preferably 500 to 650 m 2 / g.

9. The biomass conversion catalyst according to claim 1, characterized in that: The pore volume of the catalyst is 0.40 to 0.80 cm 3 / g, preferably 0.55 to 0.75 cm 3 / g.

10. A method for preparing a biomass conversion catalyst, comprising the following steps: (1) Under contact conditions, ZSM-5 molecular sieve is contacted with a treating agent for treatment, the treated material is quenched, and further separated, washed, dried and roasted to obtain material A; the treating agent is Quaternary ammonium base; (2) Under mixing conditions, the material A, the auxiliary agent and the solvent obtained in step (1) are uniformly mixed, and then separated, washed and dried to obtain material B; (3) mixing the material B obtained in step (2), the long-chain quaternary ammonium salt solution and the silicon-containing compound uniformly for reaction, and separating, washing, drying and roasting to obtain the material C after the reaction; (4) An active metal component is introduced into the material C obtained in step (3) to obtain a biomass conversion catalyst.

11. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The treating agent in step (1) is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, preferably at least one of tetraethylammonium hydroxide and tetrapropylammonium hydroxide.

12. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The treatment temperature in step (1) is 60-80° C., and the mass ratio of ZSM-5 molecular sieve to the treatment agent is 1:10-1:

50.

13. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The quenching temperature in step (1) is 0 to 10°C.

14. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The drying in step (1) is carried out at 90-110° C. for 6-12 hours. The calcination conditions in step (1) are as follows: the calcination temperature is 550-650° C. for 4-6 hours, and the calcination is carried out in an oxygen-containing atmosphere.

15. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The auxiliary agent in step (2) is one or more of polydimethyldiallyl ammonium chloride (PDDA) and polyvinyl pyrrolidone (PVP), preferably polydimethyldiallyl ammonium chloride.

16. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The solvent in step (2) is an organic solvent and an inorganic solvent, preferably an organic solvent; the organic solvent is an alcohol solution, preferably an alcohol solution with a carbon number of 1-4, selected from at least one of methanol, ethanol, and propanol, preferably ethanol, and the concentration of the alcohol is 5wt% to 25wt%; the inorganic solvent is an inorganic salt solution, selected from one or more of sodium chloride solution and calcium chloride solution.

17. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The drying in step (2) is carried out at 90-110° C. for 4-8 hours.

18. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The long-chain quaternary ammonium salt in step (3) is one or more of dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB), and octadecyltrimethylammonium bromide (STAB); preferably hexadecyltrimethylammonium bromide.

19. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The silicon-containing compound in step (3) is selected from one or more of methyl orthosilicate, ethyl orthosilicate, sodium silicate, and silica sol, preferably ethyl orthosilicate.

20. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The active metal component is introduced in step (4) by an impregnation method, preferably a step-by-step impregnation method, wherein the step-by-step impregnation method first introduces the first active metal component and then introduces the second active metal component.

21. The method for preparing a biomass conversion catalyst according to claim 20, characterized in that: The process of introducing the active metal component in step (4) is as follows: (4.1) under mixing conditions, a precursor solution of a first active metal is added dropwise to material C, and the addition of the precursor solution of the first active metal is stopped after material C just presents a mobile phase, and then the sample is treated under vacuum conditions until no bubbles are generated, and then stirred, and the treatment under vacuum conditions and stirring are repeated several times, and then a catalyst precursor is obtained after drying and calcination, wherein the drying is preferably performed under mixing conditions; (4.2) Then, a precursor solution of a second active metal is added dropwise to the catalyst precursor, and then the sample is treated under vacuum conditions until no bubbles are generated in the sample, followed by stirring. The vacuum treatment and stirring treatment are repeated several times, and then the catalyst is obtained after drying and calcining. The drying is preferably carried out under mixing conditions.

22. The method for preparing a biomass conversion catalyst according to claim 21, characterized in that: The precursor of the first active metal is an inorganic salt solution containing the first active metal, and the inorganic salt is one or more of nitrates, hydrochlorides, and sulfates, selected from one or more of nickel nitrate, cobalt nitrate, iron nitrate, iron chloride, and iron sulfate, preferably one or more of nickel nitrate, cobalt nitrate, and iron nitrate.

23. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The precursor of the second active metal is an organic acid salt solution containing the second active metal, and the organic acid salt is one or more of gluconate, lactate, and citrate; selected from one or more of magnesium gluconate, magnesium lactate, magnesium citrate, calcium gluconate, and calcium lactate, preferably one or more of magnesium gluconate and calcium gluconate.

24. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: The vacuum conditions in step (4.1) and step (4.2) are controlled to maintain a vacuum degree of 0.05 to 0.1 MPa.

25. The method for preparing a biomass conversion catalyst according to claim 10, characterized in that: In steps (4.1) and (4.2), the drying temperature is 60-100°C, and the calcination temperature is 400-600°C.

26. Use of the biomass conversion catalyst according to any one of claims 1 to 9 or the biomass conversion catalyst obtained by the biomass conversion preparation method according to any one of claims 10 to 25 in a biomass conversion process.

27. A method for non-in-situ catalytic pyrolysis of lignin residue, comprising contacting the lignin residue material with the biomass conversion catalyst according to any one of claims 1 to 9 or the biomass conversion catalyst obtained by the biomass conversion preparation method according to any one of claims 10 to 25 for reaction.

Citation Information

Patent Citations

  • Modified ZSM-5 molecular sieve catalyst for preparing light aromatic hydrocarbon through biomass pyrolysis and application

    CN105032475A

  • Double-microporous-mesoporous composite molecular sieve hydrocracking catalyst

    CN102553638A

  • Preparation method of catalytically modified catalyst of biomass tar and application of catalytically modified catalyst

    CN107008491A

  • Preparation of nickel-calcium-based composite catalyst and application thereof in biomass catalytic pyrolysis process

    CN110227468A

  • Method for refining aromatic hydrocarbons by using microporous-mesoporous core-shell structure composite molecular sieve

    CN110813370A

Cited By

  • Method for preparing hydrogen-rich synthesis gas through microwave thermocatalytic reforming of biomass pyrolysis product

    CN121493868A